Imaginaries and practices of socio-ecological breeding in traditional community forests in southern Brazil and Chile - Nicolas Floriani (Terr@ Plural, 2019)
The main objective of this text is to discuss the collective representations and cultural practices of socio-ecological reproduction of the traditional rural communities’ forests in Southern Brazil and Chile. The elements that make up the organization of local knowledge of the agroforestry community refer to common temporal and spatial scales entailed by mythopractics dimensions re-signification by the daily life of the communities investigated. The interpretation of the territorialization of the different regimes of nature on the region reveals multiple modernities that express hybridisms between practices and local and scientific knowledge that overlap in the landscape and point to alternative ways of inhabiting and breeding different naturalities.